IL-15-secreting γδT cells induce memory T cells in experimental allergic encephalomyelitis (EAE) mice. Issue 2 (August 2015) - Wang, Xiaoqian; Wei, Yinxiang; Liu, Xiaoling; Xing, Chen; Han, Gencheng; Chen, Guojiang; Hou, Chunmei; Dambuza, Ivy M.; Shen, Beifen; Li, Yan; Xiao, He; Wang, Renxi
Highlights We identified a new subset of IL-15-secreting γδT (γδT15) cells. γδT15 cells were increased in EAE mice. γδT15 induced CD44hi memory T cells by secreting IL-15. γδT15-induced memory T cells became into Th17 cells to induce EAE.